A New Approach Towards Acid Catalysts with High Reactivity Based on Graphene Nanosheets. Issue 8 (20th June 2014) - Wei, Zuojun; Yang, Yao; Hou, Yaxin; Liu, Yingxin; He, Xiaodong; Deng, Shuguang
Abstract Solid acid catalysts of graphene oxide and sulfonated graphene oxide nanosheets have been prepared by using the modified Hummers and sulfonation methods. Physical characterization indicated that a number of functional groups such as COOH, OH, O, and SO3H were introduced onto the surfaces of the as‐synthesized nanosheets. The catalytic performance of the synthesized catalysts was evaluated in the hydrolysis of the glycosidic bond and Fischer esterification. The experimental results indicated that the catalytic activity of the sulfonated graphene oxide was superior to that of other solid acid catalysts with the same or higher acid strength and has also exceeded that of H2SO4 with 9.1 times of acid strength than that of the sulfonated graphene oxide. The high reactivity can be ascribed to the formation of hydrophobic cavities through the combination of graphene sheet and the oxygen‐containing groups on its surface, which may facilitate the catalyst to anchor with reactants and promote the attack of protons.